PENANAMAN PEMAHAMAN HUBUNGAN ANTARA BILANGAN PADA SISWA BARU SEKOLAH DASAR MELALUI PEMBELAJARAN PMRI - Edo, Sri Imelda; Bulu, Vera Rosalina (Universitas Papua, 2018)
Students who have a good number sense can think and reason flexibly use numbers to solve problems, find answers that don't make sense, understand how numbers can be separated and put together in different ways, see connections between number operations, do mental calculations, and make reasonable estimates. Whereas, on the other hand, students with a poor number sense tend to depend on procedures rather than reasons, often not paying attention when answers or estimates don't make sense and have limited numerical reasoning. Therefore planting an understanding of numbers with the right method must be done early. This study aims to know how can PMRI approach context fabel construct early elementary school students understanding in finding number relation. Design research method used to reach this goal and tested in SDN Angkasa Penfui with 36 early grade 1 elementary school students as the subject. The results show that the PMRI approach using fable as a context construct students understanding in finding number relation flexibly.Â DOI:Â https://doi.org/10.30862/jhm.v1i2.1053